Oral semaglutide for the treatment of obesity: a retrospective real-world study - Krajnc, Mitja; Kuhar, Neža; Koceva, Andrijana (Frontiers in Endocrinology, 2025)
BackgroundClinical obesity is a prevalent chronic disease, significantly increasing morbidity and mortality while impairing quality of life. As diet and physical activity interventions often prove ineffective in the long term, with increasing use of pharmacotherapy, drug shortages and injection aversion present a challenge. The role of oral semaglutide at a dose of 14 mg (registered for type 2 diabetes) as a treatment for obesity in patients without diabetes remains undefined.MethodsIn the retrospective real-world study, which included 93 adults without diabetes (57% women, average age 52 years), we assessed whether treatment with 14 mg oral semaglutide over one year is associated with lower body weight, body mass index (BMI), waist circumference, blood pressure, heart rate, and obesity staging according to EOSS.ResultsOf the 93 subjects recruited, 82 (88%) were receiving oral semaglutide at a dose of 14 mg after one year. After one year of treatment body weight was significantly lower by 5.7% (5.9 kg) in completers, and BMI decreased significantly by an average of 2 kg/m². There was also a significant reduction in waist circumference by 5.5 cm and a decrease in EOSS score by 0.1. Clinically significant weight loss was achieved in 46% of all participants, with rare individuals experiencing a decrease of ≥ 15%. Adverse effects were mostly mild, with nausea reported by 23% and vomiting and diarrhoea by 12% of participants.ConclusionsObesity treatment with oral semaglutide at a dose of 14 mg showed marked interindividual variability, with approximately half achieving clinically significant reductions – mostly under 10%. Although less effective than injectable therapy, oral semaglutide at a dose of 14 mg had a favorable safety profile and may be suitable in selected clinical scenarios.